Alpha‐keratin and corneous beta protein in the parakeratinized epithelium of the tongue in the domestic goose (Anser anser f. domestica). Issue 5 (26th June 2019) - Skieresz‐Szewczyk, Kinga; Buchwald, Tomasz; Szybowicz, Mirosław; Jackowiak, Hanna
Abstract: The parakeratinized epithelium is a common epithelium in the oral cavity in birds and is characterized by the presence of cell nuclei in the cells of the cornified layer. This epithelium covers almost the entire dorsal surface of the tongue in the domestic goose apart of the lingual nail and conical papillae. So far no study has identified the molecular proteins alpha‐keratin (IF‐keratin) and/or corneous beta protein (CBP), which are responsible for keratinization or cornification processes in the parakeratinized epithelium of domestic geese. The study was performed using immunohistochemical (IHC) methods to identify alpha‐keratin. The innovative method of Raman microspectroscopy was used to determine the presence of CBP and specify their percentage in epithelial layers of the parakeratinized epithelium. The results revealed that alpha‐keratin is present in the whole parakeratinized epithelium. A strong staining reaction was detected in the basal and intermediate layers and a less strong staining reaction in the cornified layer. Raman microspectroscopy analysis confirmed the presence of alpha‐keratin and demonstrated that its percentage decreases from the basal layer to the cornified layer. The Raman microspectroscopy technique revealed the occurrence of CBP in the parakeratinized epithelium and demonstrated that the percentage of this protein increases from the basal layer to the cornified layer. Performed analysis determines that parakeratinized epithelium undergoes cornification. However, the lower percentage of CBP in the cornified layer of parakeratinized epithelium than in orthokeratinized epithelium points to the fact that parakeratinized epithelium has a weaker protective function. Abstract : While the amount of alpha‐keratin decrease from the basal layer towards the cornified layer, the amount of beta‐keratin increase from the basal layer towards the cornified layer of the parakeratinized epithelium of the tongue in the domestic goose. HIGHLIGHTS: Alpha‐keratin and corneous beta protein is present in parakeratinized epithelium. Amount of beta‐keratin increase from basal layer towards cornified layer. Parakeratinized epithelium of the tongue in birds undergoes cornification.